Pengaruh Metode Bercerita Menggunakan Media Animasi Dalam Meningkatkan Kemampuan Menyimak Anak - Wildawati, Wildawati; Saodi, Syamsuardi; Rusmayadi, Rusmayadi (Institut Agama Islam Negeri Ponorogo, 2022)
Abstract: The problem in this research is the low listening ability of children. The question is whether there is an effect of storytelling activities using animated media on children's listening skills. This study aims to determine the effect of storytelling using animation media on children's listening skills. The hypothesis in this study is that children's listening skills can develop if the storytelling method with animated media based on idol characters is applied in learning. This research approach is quantitative where the type of research is a quasi-experimental design consisting of two groups, namely the experimental group and the control group, with a non-equivalent control group design research design. The research variables were storytelling method using animation media (independent variable) and children's listening skills (dependent variable). This study took place at Al-afiah Islamic Kindergarten in Makassar, with research subjects consisting of 10 children, namely 5 children (control group) and 5 children (experimental group). Test data collection techniques, observation and documentation, with quantitative analysis. The conclusion of this study is that children's listening skills are developing